Different presurgical characteristics and seizure outcomes in children with focal cortical dysplasia type I or II - Krsek, Pavel; Pieper, Tom; Karlmeier, Anja; Hildebrandt, Michelle; Kolodziejczyk, Dieter; Winkler, Peter; Pauli, Elisabeth; Blümcke, Ingmar; Holthausen, Hans (Epilepsia, 2009)
PURPOSE: Cortical dysplasia (FCD) is a frequent cause of epilepsy in childhood. Two major pathological variants are distinguished, FCD type I and II. The aim of the study was to characterize differences between FCD type I and II with respect to imaging and EEG findings, clinical and neuropsychological presentations, and surgical outcome. METHODS: Forty children with refractory epilepsy and histopathologically confirmed FCD were retrospectively analyzed. FCD type I was identified in 24 and FCD type II in 16 patients. RESULTS: Characteristic MRI abnormalities in FCD type I included subtle white matter signal changes and regional reduction of the white matter volume. Typical MRI findings in FCD type II were increased cortical thickness, transmantle sign, gray-white matter junction blurring, fluid-attenuated inversion recovery (FLAIR) and proton density (PD) gray matter signal changes as well as T1w, and PD white matter signal changes. Continuous EEG slowing was significantly more common in patients with FCD type I. Children with FCD type I presented with lower levels of intelligence and were suffering more often from maladaptive behavior and behavioral disorders. Surgical outcome was significantly worse in the FCD type I group (seizure freedom was achieved in 21% FCD type I patients and in 75% FCD type II subjects, p < 0.001). CONCLUSIONS: Clinically important differences were found in children with distinct histopathological subtypes of FCD. Due to prominent neuropsychological deficits and worse seizure outcome, treatment strategies in FCD type I are more challenging than previously reported and these children should be recognized and specifically addressed within the incoherent group of patients with malformative brain disorders.
Keywords: hipokampus; Female; Preoperative Care; gliový fibrilární kyselý protein; Malformations of Cortical Development; imunohistochemie; Electroencephalography; radiofarmaka; mužské pohlaví; Atrophy; Retrospective Studies; magnetická rezonanční tomografie; retrospektivní studie; Humans; atrofie; elektroencefalografie; Immunohistochemistry; předoperační péče; Fluorodeoxyglucose F18; Seizures; lidé; Radiopharmaceuticals; Magnetic Resonance Imaging; pooperační péče; monoklonální protilátky; Antibodies, Monoclonal; záchvaty; Treatment Outcome; ženské pohlaví; Child; Glial Fibrillary Acidic Protein; malformace mozkové kůry; Age of Onset; fluorodeoxyglukosa F18; dítě; Hippocampus; Male; věk při počátku nemoci; výsledek terapie; Postoperative Care